The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/nar/gky192
|View full text |Cite
|
Sign up to set email alerts
|

A survey of Type III restriction-modification systems reveals numerous, novel epigenetic regulators controlling phase-variable regulons; phasevarions

Abstract: Many bacteria utilize simple DNA sequence repeats as a mechanism to randomly switch genes on and off. This process is called phase variation. Several phase-variable N6-adenine DNA-methyltransferases from Type III restriction-modification systems have been reported in bacterial pathogens. Random switching of DNA methyltransferases changes the global DNA methylation pattern, leading to changes in gene expression. These epigenetic regulatory systems are called phasevarions — phase-variable regulons. The extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(83 citation statements)
references
References 52 publications
5
67
0
Order By: Relevance
“…Our systematic analysis of REBASE identified Type I loci containing multiple hsdS genes where we detect IRs in a range of commensal organisms such as Bacteroides fragilis and multiple Ruminococcus species, in environmental bacterial species such as Leuconostoc mesenteroides , and in a number of Lactobacillus species that are important to the biotechnology and food production imdustries (Supplementary Data 3). This reflects our previous studies where we observed simple sequence repeats that mediate phase-variation in multiple Type I (38) and Type III methyltransferase genes (9) present in a variety of commensal and environmental organisms. One obvious reason for generating diversity in methyltransferase specificity is that it will increase resistance to bacteriophage.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Our systematic analysis of REBASE identified Type I loci containing multiple hsdS genes where we detect IRs in a range of commensal organisms such as Bacteroides fragilis and multiple Ruminococcus species, in environmental bacterial species such as Leuconostoc mesenteroides , and in a number of Lactobacillus species that are important to the biotechnology and food production imdustries (Supplementary Data 3). This reflects our previous studies where we observed simple sequence repeats that mediate phase-variation in multiple Type I (38) and Type III methyltransferase genes (9) present in a variety of commensal and environmental organisms. One obvious reason for generating diversity in methyltransferase specificity is that it will increase resistance to bacteriophage.…”
Section: Discussionsupporting
confidence: 88%
“…We cloned and over-expressed two hsdS alleles, alleles A and B, of the Type I inverting system that we found in S. suis (26) in order to solve the methyltransferase specificity of the Type I methyltransferases containing these HsdS proteins. We have used this approach extensively with Type III mod genes in order to solve specificity (5, 9), with the same site observed using the native protein using genomic DNA from the actual species and the over-expressed protein in E. coli (26). We only expressed HsdS alleles A and B as we do not observe any strains of S. suis with annotated genomes where either allele C or allele D (Figure 3B) is present in the hsdS expressed locus immediately downstream of the hsdM (26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In these systems, the methyltransferase (Mod) phase-varies between two states (ON or OFF) by variation in the number of SSRs in the encoding mod gene [98]. A recent survey of all Type III methyltransferases in REBASE showed that nearly 20% of Type III mod genes contain SSRs, are therefore able to phase-vary, and potentially able to control a phasevarion [99]. mod genes are highly conserved (>95% DNA sequence identity) in their 5 0 and 3 0 regions, but contain a highly divergent central domain, the TRD (for Target Recognition Domain).…”
Section: Phase-variable Dna Methyltransferasesmentioning
confidence: 99%